Role of Frozen Section Examination in the Management of Testicular Nodules: A Useful Procedure to Identify Benign Lesions - Bozzini, Giorgio; Rubino, Barbara; Maruccia, Serena; Marenghi, Carlo; Casellato, Stefano; Picozzi, Stefano; Carmignani, Luca (Urology Journal, 2014)
Abstract Purpose: To assess the validity of frozen section examination (FSE) on testis nodules. Materials and Methods: A series of 86 preselected patients with testicular nodules were recruited in this study. Nodules smaller than 2 cm had been surgically removed and biopsies of the margins performed. Larger nodules were just biopsied. Orchiectomy was the treatment of choice for malignant lesions and stromal tumors. Conservative surgery was performed on 2 previously monorchid patients with Leydig cell tumor because of the presence of just one testis. Conservative surgery was the treatment of choice for benign lesions in 32 cases. Results: At FSE we observed that nodules were malignant germinal tumors in 47% of the cases, stromal tumors in 7% of the cases, benign lesions in 45% of the cases and doubtful for lymphoproliferative lesion in 1 case. The diagnosis made by FSE were confirmed in the definitive ones in all of them, we reported just 2 cases of Leydig cell tumor and benign fibrosis lesion. In these 2 cases, definitive histology of the collected specimens revealed areas of Leydig cell hyperplasia and seminomatous foci, respectively. Conclusion: Our data suggest that FSE is a valid tool to discriminate between benign and malignant neoplastic lesions, particularly when an adequate sample is available.